Evaluation of the integrated community based home care model - LR Uys (AOSIS, 2001)
In 1999-2000 the Integrated Community-Based Home Care model for the care of people with AIDS in communities were implemented in seven sites across the country. The post-implementation evaluation showed that most respondents felt that the model could be replicated if a functioning and informed network including all partners, and a strong management team were in place. The effects of the project were mainly positive for all stakeholders (hospice, clinic, hospital, PWA and their carers, professionals and other community members). Hospitals and community- based services became more aware of and involved in the needs of PWA and felt that the model enabled them to address these needs. PWA and their carers felt supported and respected.